2010
DOI: 10.4238/vol9-2gmr817
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication The functional polymorphisms -429T>C and -374T>A of the RAGE gene promoter are not associated with gestational diabetes in Euro-Brazilians

Abstract: ABSTRACT. The receptor for advanced glycation end products (RAGE or AGER) is a multiligand member of the immunoglobulin superfamily. RAGE is expressed in several tissues, including human myometrium, chorionic villi and placenta. Advanced glycation end products are the best studied ligands of RAGE; they have proinflammatory actions in human gestational tissues, increasing oxidative stress and the release of cytokines and prostaglandins. We RAGE SNPs and gestational diabetes investigated the association of RAGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Clinical characteristics and biochemical parameters (Table 2) of the studied groups were similar to those reported in other studies (Santos et al, 2010a). GDM patients were usually heavier since overweight is a risk factor associated with this pathology and type 2 diabetes (Rosenberg et al, 2005;Rivero et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…Clinical characteristics and biochemical parameters (Table 2) of the studied groups were similar to those reported in other studies (Santos et al, 2010a). GDM patients were usually heavier since overweight is a risk factor associated with this pathology and type 2 diabetes (Rosenberg et al, 2005;Rivero et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…The rs1800624 SNP is associated with a threefold increase in AGER expression in vitro , including sRAGE expression. sRAGE serves as an endogenous antagonist by neutralizing proinflammatory ligands that are in turn unable to activate inflammatory pathways [85]. Absolute or strong linkage disequilibrium, depending on the studies, was found between promoter polymorphisms: rs1800625 (−429T>C), rs1800624 (−374T>A), and a 63 bp deletion [29].…”
Section: Rs1800624 Nm_0011364:c-388t>a Polymorphismmentioning
confidence: 99%
“…A protective effect of rs1800624 against diabetic retinopathy in type 2 diabetic patients was identified in a meta-analysis [42]. On the other hand, a study on Caucasian Brazilians with type 2 diabetes did not find any association between the presence of the A allele and diabetic retinopathy, diabetic nephropathy, or ischemic heart disease [93], while other reports did not find any association between rs1800264 and cardiovascular diseases or diabetes [85]. No association was found between rs1800264 and the presence of heart failure in unselected patients and between rs1800264 and higher mortality in those with heart failure [94].…”
Section: Rs1800624 Nm_0011364:c-388t>a Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of human genes was investigated dealing with GDM: HLA, SUR1 (sufonylurea receptor gene), GCK (glucokinase gene), TCF7L2 (transcription factor 7-like 2 gene), HFE (hemochromatosis gene) and others with contradicting results [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%